ANALISIS YURIDIS PERJANJIAN PERDAGANGAN BEBAS BERBASIS DIGITAL (DIGITAL FTA) TINJAUAN ATAS KERANGKA HUKUM MULTILATERAL DAN REGIONAL DI ERA EKONOMI DIGITAL - Rahmat Wijaya; Annie Myranika; Gunarto Wardono; Agus Alqodri; Raliyanto Budi Wikarno (CV. Lafadz Jaya, 2026)
The exponential growth of the digital economy has driven a fundamental transformation in the architecture of international trade, leading to the emergence of digital-based Free Trade Agreements (FTAs) or Digital Trade Agreements (DTAs). This study comprehensively analyses the legal framework of digital-based free trade agreements, focusing on three main aspects: (1) the evolution of digital regulation within the context of international trade law; (2) the harmonisation of digital standards between the models of the United States, the European Union, and ASEAN; and (3) the legal implications of the ASEAN Digital Economy Framework Agreement (DEFA) for Indonesia’s national legal system. Using a normative legal research method with a comparative approach and document analysis, this study examines 193 Regional Trade Agreements (RTAs) containing e-commerce provisions that have been notified to the WTO up to 2024. The findings reveal regulatory fragmentation between the US data liberalisation model, which is market-oriented, and the European Union’s privacy protection model, which is based on fundamental rights. The ASEAN DEFA 2025 represents a legal innovation as the world’s first comprehensive regional digital economic agreement, yet faces implementation challenges regarding digital sovereignty, cross-border data protection, and regulatory capacity gaps among member states. This study recommends the development of a hybrid legal model that accommodates the digital development interests of developing nations without compromising regional economic integration.